﻿A revision of Centrioncus Speiser (Diptera, Diopsidae, Centrioncinae) with descriptions of new species from Angola, Burundi, and Kenya - Hans R. Feijen; Cobi Feijen (ZooKeys, 2023)
A diagnosis is presented for the Centrioncinae, the Afromontane Forest Flies or stalkless Diopsidae, while its taxonomic position within the Diopsidae is discussed. Arguments are presented for an eventual raising of the Centrioncinae to family level. The differential characters for its two genera, Centrioncus Speiser and Teloglabrus Feijen, are tabulated. The diagnosis for Centrioncus is updated and a key to the ten species now recognised (including three new species) is provided. Centrioncus crassifemur sp. nov. is described from a single female from Angola. This greatly extends the distribution range for the genus. Centrioncus bururiensis sp. nov. is described from Burundi, while Centrioncus copelandi sp. nov. originates from the Kasigau Massif of Kenya. Diagnoses, descriptive updates, illustrations and notes are presented for all other Centrioncus. Centrioncus aberrans Feijen, described from Uganda, is now also recorded for western Kenya, Rwanda, and possibly eastern DR Congo. This wide range of C. aberrans is unusual for the Centrioncinae species which have allopatric and usually very restricted distribution ranges. Defining characters of C. aberrans from the various regions were examined in detail, but only minor differences were found. Centrioncus decoronotus Feijen, described from Kenya, is now recorded for several other places in Kenya. A distribution map is given for the Eastern African Centrioncus species. The eastern branch of the Great Rift Valley appears to form a barrier between C. aberrans and C. decoronotus. The type species of the genus, C. prodiopsis Speiser from the Kilimanjaro in Tanzania, was only known from the 1905–1906 type series. After more than 100 years it has now been found again on the Kenya side of Kilimanjaro. Various differential characters of Centrioncus and Diopsidae are discussed, while brief discussions on sex ratio and fungal parasites are given. Centrioncus are known to occur on low shrubs and herbaceous plants in rain forests. Now, the possibility is indicated that they also might occur higher up in the tree canopies.